A single‐arm, non‐randomized investigation into the short‐term effects and follow‐up of a 4‐week lower limb exercise programme on kinesiophobia in individuals with knee osteoarthritis. (24th January 2020) - Molyneux, Jimmy; Herrrington, Lee; Riley, Ben; Jones, Richard
Abstract: Objective: To investigate the short‐term effects and follow‐up of a 4‐week lower limb exercise programme on kinesiophobia in individuals with knee osteoarthritis (OA). Design: Participants diagnosed with knee OA clinically against the American College of Rheumatology criteria were recruited. Participants completed a 4‐week lower limb exercise programme. Each participant completed two questionnaires, the Tampa Scale of Kinesiophobia and the Knee Injury and OA Outcome Score. Each measurement was completed at the baseline assessment, at Session 4 of the programme, at Session 8 of the programme, and 6 weeks after the exercise programme. Perceived levels of exertion rate of perceived exertion were measured after each exercise session using the modified Borg scale. Results: Fifty‐four participants took part in the study. Kinesiophobia decreased from the baseline assessment to 6 weeks after the exercise programme. KOOS pain, symptoms, sports and recreation, quality of life and activities of daily living score increased, therefore showed improvement. Correlational analysis highlighted a moderate negative correlation between the KOOS pain and kinesiophobia at baseline and 6 weeks after the exercise programme (0.44 and 0.48 respectively). Conclusions: Understanding baseline kinesiophobia scores could provide an important resource for health professionals who manage individuals with knee OA to improve the quality of care due to the correlation with pain changes and may improve exercise‐related outcomes for a longer duration. Highlights: Kinesiophobia is prevalent in individuals diagnosed with knee osteoarthritis (OA). Kinesiophobia decreased in 75% of individuals with knee OA after a 4‐week exercise programme. Correlation between pain and kinesiophobia at baseline and 6 weeks after an exercise programme. An understanding of an individual's kinesiophobia level before an exercise programme is important for future prognosis of changes in pain. Clinical Trial Number: NCT02734342